Immigrant Performance in the Labour Market: Bonding and Bridging Social Capital - Bram Lancee (Amsterdam University Press, 2012)
To what extent can different forms of social capital help immigrants make headway on the labour market? An answer to this pressing question begins here. Taking the Netherlands and Germany as case studies, the book identifies two forms of social capital that may work to increase employment, income and occupational status and, conversely, decrease unemployment. New insights into the concepts of bonding and bridging arise through quantitative research methods, using longitudinal and crosssectional data. Referring to a dense network with 'thick' trust, bonding is measured as family ties, co-ethnic ties and trust in the family. Bridging is seen in terms of interethnic ties, thus implying a crosscutting network with 'thin' trust. Immigrant Performance in the Labour Market reveals that although bonding allows immigrants to get by, bridging enables them to get ahead. – – De auteur analyseert de invloed van de verschillende vormen van soorten sociaal kapitaal op de arbeidsmarktintegratie van immigranten in Duitsland en Nederland. Centraal staat de vraag: hoe kunnen migranten profiteren van sociale verhoudingen tussen de autochtone bevolking en de eigen etnische groep? Het boek levert een cruciale bijdrage aan Migratie Studies door het conceptualiseren van 'bonding' en 'bridging' als elementen van sociaal kapitaal. Door grondige analyse van methoden en data onderzoekt Lancee of 'bonding' en 'bridging' immigranten vooruithelpen op de arbeidsmarkt. Bovendien biedt het boek een vergelijking tussen Duitsland en Nederland waardoor de bevindingen in een context geplaatst kunnen worden.
Keywords: 300; sociology; sociologie; ethnic group; Germany; labour economics; Netherlands; occupational prestige; social capital